Policies and Procedures Review of the Management of Account Receivable in Swiss-Belhotel Harbour Bay Batam - Mega Mayasari; Angga Andrian (Pusat P2M Politeknik Negeri Batam, 2016)
This research aims to find out how the management of accounts receivable in Swiss-Belhotel Harbour Bay Batam run followed the existing policies and procedures. This is a qualitative research with descriptive analysis. The method of data collection was done through observation and documentation. Study results has concluded that credit given without a contract between company and customers raise the highest risk of accounts receivable loss. In addition, there is no strict sanctions for the delay settlement of account receivable. This research suggests that the company should follow the procedures that exist in case granting of the credit facilities and provide strict sanctions over the late paid of account receivable.